2019
DOI: 10.1136/bmjopen-2019-029810
|View full text |Cite
|
Sign up to set email alerts
|

Fostering humanism: a mixed methods evaluation of the Footprints Project in critical care

Abstract: ObjectivesThe objectives of this mixed-methods study were to assess the uptake, sustainability and influence of the Footprints Project.SettingTwenty-two-bed university-affiliated ICU in Hamilton, Canada.ParticipantsICU patients admitted and their families, as well as clinicians.InterventionsWe developed a personalised patient Footprints Form and Whiteboard to facilitate holistic, patient-centred care, to inform clinical encounters, and to create deeper connections among patients, families and clinicians.Outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Our methods were informed by recent narratives and innovations ( 39–43 ). The high clinician participation rate allowed documentation of professional observations and personal experiences in the context of goal-concordant care ( 44 ) and practice-based interventions promoting personhood ( 12 , 20 , 26 ), also operating elsewhere ( 15–17 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our methods were informed by recent narratives and innovations ( 39–43 ). The high clinician participation rate allowed documentation of professional observations and personal experiences in the context of goal-concordant care ( 44 ) and practice-based interventions promoting personhood ( 12 , 20 , 26 ), also operating elsewhere ( 15–17 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…At this institution, typical end-of-life care includes interventions designed to humanize the experience for patients and families as built into the daily workflow and staff training ( 16 ). To learn more about each patient, the clinical team telephoned family members, collating personal information about patients to share with staff via a whiteboard and in the electronic medical record (EMR) ( 12 ), which served to reassure families that the staff was interested in their loved one as a person ( 20 ). Building on this information in recognition of each dying patient, staff elicited and implemented final wishes ( 15 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Close communication between families of acutely ill patients has been shown to improve psychological outcomes and lead to higher quality surrogate decision making surrounding the direction of care. 39,40 Electronic communication through phone calls or video conferencing was widely adopted by health care systems during the COVID-19 pandemic. 28 A study that evaluated the feasibility and acceptability of electronic communication for palliative care family meetings found that 80% of family members felt comfortable articulating questions and expressing thoughts throughout the meeting.…”
Section: Connecting With the Health Care Teammentioning
confidence: 99%